2019
DOI: 10.2134/agronj2018.08.0489
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Content and Use Efficiency of Sweet Sorghum Grown in the Lower Midwest

Abstract: Optimizing N fertilizer inputs is imperative for improving sweet sorghum [Sorghum bicolor (L.) Moench] yields and biofuel feedstock system efficiency. A 2‐yr study was conducted to determine the physiological N‐use efficiency (NUE) response in sweet sorghum's ethanol yield of stem juice, bagasse, and total ethanol yield (TEY). Two sweet sorghum cultivars (‘Dale’ and ‘Top 76–6’) were fertilized at five N fertilizer rates (0, 56, 112, 168, and 224 kg ha−1). At harvest, the stem juice and bagasse yields were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…As a result, with higher soil moisture under energy sorghum, the mid‐season peak in N 2 O fluxes was higher for energy sorghum than maize, leading to comparable cumulative growing season N 2 O fluxes for the two crops. Recent evidence also suggests that optimum N fertilization rates for energy sorghum are approximately 56 kg N ha −1 (Maw et al, 2019; Schetter et al, 2020), which is closer to the rate applied to miscanthus in this study. It is therefore likely that our energy sorghum fertilization rate exceeded plant N requirements, and thus we would expect N 2 O losses to be reduced with less N addition in future.…”
Section: Discussionsupporting
confidence: 80%
“…As a result, with higher soil moisture under energy sorghum, the mid‐season peak in N 2 O fluxes was higher for energy sorghum than maize, leading to comparable cumulative growing season N 2 O fluxes for the two crops. Recent evidence also suggests that optimum N fertilization rates for energy sorghum are approximately 56 kg N ha −1 (Maw et al, 2019; Schetter et al, 2020), which is closer to the rate applied to miscanthus in this study. It is therefore likely that our energy sorghum fertilization rate exceeded plant N requirements, and thus we would expect N 2 O losses to be reduced with less N addition in future.…”
Section: Discussionsupporting
confidence: 80%
“…This study showed a similar range of PNUE (78.1 -256.4 kg DM kg -1 ) to the reports from Grennel et al (2014) [64] and Maw et al (2017) [34], and the PNUE likely improved with the low N input [34,65,66]. Although the N effect on NIE and NRE was not significant in this study, the better NIE and NRE likely occurred at the low N-rate [34,56,65,66,69]. Many studies have shown that the biomass sorghum has a low N fertilizer requirement (mostly < 120 kg-N ha -1 ) for optimizing biomass yield with desirable feedstock quality for biofuel productions [29,56,57,[67][68][69].…”
Section: Nitrogen Effects and Use Efficiencysupporting
confidence: 89%
“…Although the N effect on NIE and NRE was not significant in this study, the better NIE and NRE likely occurred at the low N-rate [34,56,65,66,69]. Many studies have shown that the biomass sorghum has a low N fertilizer requirement (mostly < 120 kg-N ha −1 ) for optimizing biomass yield with desirable feedstock quality for biofuel productions [29,56,57,6769]. Moreover, the biomass yield, PNUE, and NIE can be further improved by extending the growing season [11,12,31].…”
Section: Discussionmentioning
confidence: 69%
“…However, most studies focused on comparing plants growing under high-N versus low-N conditions, while the microbiome changes between different plant genotypes in the context of varying soil N levels has not been widely investigated. In sorghum, there is a huge variation in tolerance to N stress between genotypes [ 28 ]. Despite the fact that root-associated microbial communities of sorghum change between N-levels [ 24 , 26 , 27 ], the natural variability of the microbiome between N-stress tolerant and sensitive sorghum genotypes is unclear.…”
Section: Introductionmentioning
confidence: 99%